2020
DOI: 10.3390/jfb11040076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functional Silver Nanoparticles and Microparticles with Modifiers and Evaluation of Their Antimicrobial, Anticancer, and Antioxidant Activity

Abstract: An accumulating body of evidence reports the synthesis and biomedical applications of silver nanoparticles. However, the studies regarding the use of maleic acid and citric acid in the synthesis of nano-sized silver particles (AgNPs) and micro-sized silver particles (AgMPs) as well as their antibacterial, antifungal, and anticancer activities have not been reported. In the current study, we synthesized AgNPs and AgMPs using maleic acid and citric acid as capping agents and have characterized them by UV-Vis, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 94 publications
2
24
0
Order By: Relevance
“…This behavior was also observed in the MIC determinations, where Ag 2 Fe 2 O 2 antifungal effects were observed at 50 mg/mL, Ag 2 Cr 2 O 4 at 12.5 mg/mL, and fluconazole at 25 mg/mL against all four fungal species. Dilshad et al [74] observed the antimicrobial effect of citric acid-and maleic acid-capped AgNPs against A. niger, A. flavus, A. fumigatus, and Fusarium solani. The authors observed that the maleic acid-capped NPs exhibit better antifungal activity than citric acid-capped NPs.…”
Section: Organic Materials-based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior was also observed in the MIC determinations, where Ag 2 Fe 2 O 2 antifungal effects were observed at 50 mg/mL, Ag 2 Cr 2 O 4 at 12.5 mg/mL, and fluconazole at 25 mg/mL against all four fungal species. Dilshad et al [74] observed the antimicrobial effect of citric acid-and maleic acid-capped AgNPs against A. niger, A. flavus, A. fumigatus, and Fusarium solani. The authors observed that the maleic acid-capped NPs exhibit better antifungal activity than citric acid-capped NPs.…”
Section: Organic Materials-based Nanoparticlesmentioning
confidence: 99%
“…AgNPs Growth inhibition at 10 µg/mL [33] 54% growth inhibition at 100 mg/L [92] 75.61% growth inhibition at 150 µg/mL [105] Growth inhibition at 150 µg/mL [106] Growth inhibition at 40 µg/mL [107] 60% growth inhibition at 50 µg/mL [110] Marketed AgNPs 90% growth inhibition at 0.5 µg/mL (clinical isolates) [93] AgO/Ag NPs 75.25% growth inhibition at 50 µg/mL [113] Ag-AuNPs 90.78% growth inhibition at 200 µg/mL [111] Ag 2 Cr 2 O 4 3.1 times higher inhibition than fluconazole [94] Maleic acid capped AgNPs Growth inhibition [74] Milk protein synthesized AgNPs Growth inhibition [95] Fibroin-AgNPs Fungicidal activity at 2 µg/mL [99] Ag-Cu core-shell NPs Growth inhibition at 0.1 M and fungicidal activity at 15 µg/mL [100] CChG/AgNPs Better growth inhibition than AmB at 0.98 µg/mL [101] CuNPs Growth inhibition at 31.67 µg/mL [107] Cu-Ag core-shell NPs Growth inhibition at 0.1M and fungicidal activity at 25 µg/mL [100] Au@5FU NPs Higher inhibition than 5FU [96] Fibroin-AuNPs Fungicidal activity at 10 µg/mL [99] TiO 2 -PLA NPs 99.9% growth inhibition at 8 wt% of NPs [97] pMWCNT-CD/Ag-TiO 2 nanosponge Growth inhibition at 437.5 µg/mL [98] Table 3. Cont.…”
Section: Nanomaterials Antifungal Effect Referencementioning
confidence: 99%
“…DAPI and propidium iodide were purchased from Sigma. Two fluorescent dyes that selectively penetrate the cell membranes and fluoresce at different wavelengths were used in the 7-Chloro-4,6-dinitrobenzofuroxan 1 was synthesized according to the literature [47], 4,6-dinitro-7-(thiazol-2-ylamino)benzo[c] [1,2,5]oxadiazole 1-oxide 3a was prepared according to [20], and 2-aminothiazoles were purchased by Sigma-Aldrich (Darmstadt, Germany).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…The end result of the action of all antitumor drugs is the inhibition of cell proliferation and the death of tumor cells (tumor regression) [ 5 ]. This effect is achieved by acting on various targets in the cell: DNA; RNA; enzymes necessary for normal DNA replication and repair; pathways for the intracellular transduction of mitogenic signals; the mitotic apparatus of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…It should also provide functional groups which can be further modified to control the drug release or to bind targeting units [11]. Silver nanoparticles based nanosystems were evaluated as suitable carriers of various therapeutic molecules, including antiinflammatory [12,13], antioxidant [14], antimicrobial [15,16] and anticancer [17,18] substances. Coreshell nanoparticles have received a lot of attention, especially as multimodal for medical applications [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%